Mechanism investigation for poloxamer 188 raw material variation in cell culture. (27th April 2016) - Peng, Haofan; Ali, Amr; Lanan, Maureen; Hughes, Erik; Wiltberger, Kelly; Guan, Bing; Prajapati, Shashi; Hu, Weiwei
Abstract : Variability in poloxamer 188 (P188) raw material, which is routinely used in cell culture media to protect cells from hydrodynamic forces, plays an important role in the process performance. Even though tremendous efforts have been spent to understand the mechanism of poloxamer's protection, the root cause for lot‐to‐lot variation was not clear. A recent study reported that the low performance was not due to toxicity but inefficiency to protect cells (Peng et al., Biotechnol Prog. 2014;30:1411–1418). In this study, it was demonstrated for the first time that the addition of other surfactants even at a very low level can interfere with P188 resulting in a loss of efficiency. It was also found that the performance of P188 lots correlated well with its foam stability. Foam generated from low performing lots in baffled shaker flask lasts longer, which suggests that the components in the foam layers are different. The spiking of foam generated from a low performing lot into the media containing a high performance lot resulted in cell damage and low growth. Analytical studies using size exclusion chromatography (SEC) identified differences in high molecular weight (HMW) species present in the P188 lots. These differences are much clearer when comparing the HMW region of the SEC chromatogram of foam vs. bulk liquid samples. This study shows that low performing lots have enriched HMW species in foam samples due to high hydrophobicity, which can be potentially used as a screening assay. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:767–775, 2016